2019
DOI: 10.1002/mdc3.12723
|View full text |Cite
|
Sign up to set email alerts
|

Postural Abnormality in Parkinson's Disease: A Large Comparative Study With General Population

Abstract: Background Postural abnormalities in Parkinson's disease (PD) patients and unimpaired elderly are not well differentiated. Factors related to postural abnormality associated with PD are controversial. Objective We assessed differences in postural change between PD patients and unimpaired elderly and elucidated factors related to abnormal posture in PD patients. Methods We measured the dropped head angle (DHA), anterior flexion angle (AFA), and lateral flexion angle (LFA) of the thoracolumbar spine of an unprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…There is a report of improvement in 34 of 138 patients with camptocormia after discontinuation of pramipexole, 25 and there has been a dopaminergic drug dose‐control study showing improvement of patients with Pisa syndrome 26 . Although no noticeable difference has been found in affinity between non‐dopamine drugs, 27 the effects of anti‐PD drug administration on abnormal posture have not been established. Although these studies have targeted severe postural abnormalities such as camptocormia at a trunk flexion angle of 45° or more and Pisa syndrome with trunk flexion of 10° or more, the LTF has ranged from 1° or more to severe bending.…”
Section: Discussionmentioning
confidence: 99%
“…There is a report of improvement in 34 of 138 patients with camptocormia after discontinuation of pramipexole, 25 and there has been a dopaminergic drug dose‐control study showing improvement of patients with Pisa syndrome 26 . Although no noticeable difference has been found in affinity between non‐dopamine drugs, 27 the effects of anti‐PD drug administration on abnormal posture have not been established. Although these studies have targeted severe postural abnormalities such as camptocormia at a trunk flexion angle of 45° or more and Pisa syndrome with trunk flexion of 10° or more, the LTF has ranged from 1° or more to severe bending.…”
Section: Discussionmentioning
confidence: 99%
“…However, also in that study, only 37% of the variance of the stimulation effect was predicted (7). A study with a great number of PD patients found age, duration of disease, H-Y stage, pain, and vertebral disease relevant, but without further specification of their individual relevance (18).…”
Section: Discussionmentioning
confidence: 99%
“…These episodes are due in part to chronic levodopa therapy, which is one of the disease’s most common treatment methods. These episodes consist of both motor, non-motor, posture, and autonomic symptoms [ 3 , 7 ]. Patients with off-episodes also report anxiety about impending symptoms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%